Calculation Of Gruneisen Parameter, Compressibility, And Bulk Modulus as Functions Of Pressure In (C6H5CH2NH3)2 PBI4 - Arzu Kurt (Journal of Advanced Research in Natural and Applied Sciences)
Hybrid organic-inorganic perovskites (HOIPs) exhibit multiple structural phase transitions, which result in enhanced mechanical and electronic properties of these perovskites. Order-disorder of organic components was thought to be the main factor to cause these phase transitions up to the last decade; however, recent research about HOIPs have shown that the structural phase transition also occurs with the induced pressure or temperature. The research studies related to the pressure have attracted a great deal of scholarly interest due to its contribution to the func-tionality of HOIPs in many current applications. Two-dimensional halide perovskites having been synthesized in the last few years have been increasingly studied thanks to its superior hysteresis in flexibility and mechanical properties under pressure. It is important to understand and model theoretically how induced pressure affects mechanical and electronic properties of (PMA)2PbI4 in order to develop new potential applications in optoelectronics. In this study, the isothermal mode-Grüneisen parameter, the isothermal compressibility, and the bulk modulus were calculated as functions of pressure at ambient temperature by using the calculated Raman frequencies and observed volume data for the selected IR modes in (PMA)2PbI4. These calculated parameters were compared with the observed measurements reported for the Pbca, Pccn and Pccn (isostructural) phases in the studied perovskites. The results obtained in the present study, which were highly compatible with the experimental measurements, showed that (PMA)2PbI4 is usable in optoelectronic applications.